Measurement of Prompt D⁰, Λ⁺c, and Σc⁰ʼ⁺⁺ (2455) Production in Proton-Proton Collisions at √s = 13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akbar, Z.; et al. (American Physical Society, 2022)
The Pᴛ-differential production cross sections of prompt D⁰, Λ⁺c, and Σc⁰ʼ⁺⁺ (2455) charmed hadrons are measured at midrapidity (|y| < 0.5) in pp collisions at √s = 13 TeV. This is the first measurement of Σc⁰ʼ⁺⁺ production in hadronic collisions. Assuming the same production yield for the three Σc⁰ʼ⁺ʼ⁺⁺ isospin states, the baryon-to-meson cross section ratios Σc⁰ʼ⁺ʼ⁺⁺/D⁰ and Λ⁺c/D⁰ are calculated in the transverse momentum (Pᴛ) intervals 2 < Pᴛ < 12 and 1 < Pᴛ < 24 GeV/c. Values significantly larger than in e⁺e⁻ collisions are observed, indicating for the first time that baryon enhancement in hadronic collisions also extends to the Σc. The feed-down contribution to Λ⁺c production from Σc⁰ʼ⁺ʼ⁺⁺ is also reported and is found to be larger than in e⁺e⁻ collisions. The data are compared with predictions from event generators and other phenomenological models, providing a sensitive test of the different charm-hadronization mechanisms implemented in the models.
Keywords: Physics; https://purl.org/pe-repo/ocde/ford#1.03.00